UPAYA PENINGKATAN KOMPETENSI DASAR LISTRIK SISWA SMK MELALUI PEMBUATAN CATU DAYA VARIABLE - Asnil Asnil; Habibullah Habibullah; Irma Husnaini; Fivia Eliza (Universitas Negeri Padang, 2019)
SMK N 1 Painan and SMK N 1 Koto XI Tarusan develops a new study program namely Audio Video Engineering, one of the objectives is to prepare students to have the skills to enter employment. Based on the results of surveys and interviews conducted with the school, the problems that are being faced are where the Audio Video Technique is more directed to the electronic field but in all teaching and learning activities, especially practical activities using electrical-related equipment, such as power supplies. The power supply is a basic knowledge of electricity that is not specifically studied in the field of Audio Video Engineering. Likewise, during the Industrial Work Practice, the same problems were encountered in the field. Overcoming these problems is held a skills training carried out in the form of theory and practice to increase knowledge about how to design power supplies, calculate the needs of components and assemble power supplies. A power supply that will be made with variable output or variable. The training was targeted to produce a product in the form of a Power Supply prototype. This product is expected to be used by the next student as a place to increase knowledge about the power supply. Good for the learning process in the classroom, especially practical learning or as preparation for students who will do industrial practice or internship so that existing problems can be addressed properly.